Simultaneous adsorption and degradation of bisphenol A on magnetic illite clay composite: Eco-friendly preparation, characterizations, and catalytic mechanism. (10th March 2021) - Bao, Teng; Damtie, Mekdimu Mezemir; Wei, Wei; Phong Vo, Hoang Nhat; Nguyen, Khanh Hoang; Hosseinzadeh, Ahmad; Cho, Kuk; Yu, Zhi Min; Jin, Jie; Wei, Xing Lai; Wu, Ke; Frost, Ray L.; et al.
Abstract: Excess bisphenol A (BPA) is a pollutant of concern in different water sources. In this work, magnetic illite clay-composite material (Fe3 O4 @illite) was synthesized via the coprecipitation method by loading Fe3 O4 nanoparticles (nano-Fe3 O4 ) onto the surfaces of illite clay. Results from different characterizations showed that nano-Fe3 O4 was embedded into illite clay nanosheets and existed on the surfaces of illite clay, thereby reducing the degree of agglomeration and improving dispersibility. The catalytic BPA degradation of Fe3 O4 @illite and nano-Fe3 O4 confirmed the superior performance of Fe3 O4 @illite compared with that of nano-Fe3 O4 . The optimum operating parameters for degradation were 0.3 mL of H2 O2 at pH of 3 in the presence of Fe3 O4 @illite, which provided a maximum degradation capacity up to 816, 364, 113, and 68 mg/g for epoxy BPA concentration of resin wastewater (266 mg/L), synthetic wastewater (80 mg/L), Hefei City swan lake (25 mg/L), and Hefei University lake wastewater (14.94 mg/L), respectively, in 180 min reaction time. The degradation data conformed to the pseudo-first-order kinetic model. The degradation pathways and mineralization study revealed that the adsorption-Fenton-like reaction was the principal mechanism that demonstrated 100% degradation efficiency of Fe3 O4 @illite even after nine successive runs. The regeneration and reusability tendency analysis ensured that Fe3 O4 @illite can be easily separated by using magnets. Therefore, Fe3 O4 @illite composite with H2 O2 Fenton-like technology was a promising method for BPA degradation. Graphical abstract: Image 1 Highlights: Fe 3 O 4 @illite was successfully synthesized via a simple co-precipitation . The maximum degradation capacity of Fe3 O4 @illite reached up to 364 mg/g. Adsorption and Fenton-like oxidation were dominant removal mechanism . BPA removal remained 100% after nine successive runs . Magnetic separation of Fe3 O4 @illite was possible as a regeneration mechanism.